Dampak Sosial Politik terhadap Perkembangan Ekonomi Umat Allah Zaman Perjanjian Lama - Karel Siahaya (JURNAL TERUNA BHAKTI, 2019)
This is a study of the Old Testament about the economic development of the Old Testament Israelites which was influenced by several things such as social politics. The purpose of this discussion is to show the social, potent and even geographical influences on the economic development of the people. By using descriptive methods, the conclusion obtained from this study is, political power will have an impact on the economic development of the people in it. Likewise, with social, there is a development of social structures based on the economy. Abstrak Ini adalah sebuah kajian Perjanjian Lama tentang perkembangan ekonomi umat Israel zaman Perjanjian Lama yang dipengaruhi oleh beberapa hal seperti sosial politik. Tujuan pembahasan ini adalah untuk menunjukkan pengaruh sosial, potik, bahkan geografi terhadap perkembangna ekonomi umat. Dengan menggunakan metode deskriptif, kesimpulan yang diperoleh dari kajian ini adalah, kekuasaan politik akan memberikan dampak bagi perkembangan ekonomi umat di dalamnya. Demikian juga dengan sosial, terjadi perkembangan struktur sosial berdasarkan ekonomi.